EFFECT OF NATURAL ASCORBIC ACID ON PERFORMANCE AND CERTAIN HAEMATO-BIOCHEMICAL VALUES IN LAYERSEXPOSED TO HEAT STRESS - Alaeldein M. Abudabos; Abdullah N. Al-Owaimer; Elsayed O.S. Hussein; Mutahar H. Ali; Muath Q. Al-Ghadi (Journal of Animal and Plant Sciences, 2018)
A four week trial examined the effects of dietary vitamin C supplement (200 mg/kg) and heat stress on performance of layers and blood biochemical profile. Two levels of environmental temperatures: thermoneutral (TN, 22°C) and high temperature (HT, 32°C) and two levels of vitamin C supplement (without and with) were arranged in a factorial arrangement resulted in four dietary treatments on feed intake (FI), egg mass (EM), feed conversion ratio (FCR), egg shell strength (ESS) and blood hematology in one strain of layers (Hy-Line W-36) from 65 to 69 weeks of age.  Four treatments were assigned to nine replicates with three hens per pen. Treatment 1 was a corn-soy control in TN, treatment 2 was control in HS, treatment 3 was control + 0.2 g/l ascorbic acid in TN and treatment 4 was control + 0.2 g/l ascorbic acid in HS. Hens which were subjected to TN environment had higher FI as compared to those which had subjected to HS environment (P < 0.05).  Egg mass was not affected by vitamin C, temperature or their interaction (P > 0.05). Feed conversion ratio was affected by temperature but not with Vitamin C supplementation.  Hens which were subjected to TN had better FCR as compared to those which were subjected to HS for weeks two, three, four and cumulative period (P≤0.01; P≤0.05; P≤0.01; P≤0.01, respectively). Hens which were subjected to HS had weaker shell strength at week two (P≤0.01), week four (P≤0.05) and cumulative period (P≤0.001). On the other hand, there was a significant interaction for vitamin C x Temperature at week three (P≤0.001). Vitamin C increased Na and P concentrations in serum (P≤0.05, P≤0.01, respectively) and decreased Ca and P concentrations as compared to those which were subjected to TN (P≤0.05, P≤0.05, respectively). It can be concluded that natural vitamin C did not have a major impact on cumulative performance or plasma mineral status.
Keywords: Heat stress; thermoneutral; vitamin C; layers; Feed conversion ratio (FCR); Hen performance